2010
DOI: 10.1016/j.rbmo.2009.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin and retinol-binding protein 4 concentrations in lean, glucose-tolerant women with PCOS

Abstract: Since insulin resistance is accepted to be a common feature of polycystic ovary syndrome (PCOS), the exact molecular mechanism(s) involved in glucose and lipid metabolism have been under investigation in the syndrome. Recently, two novel adipokines, namely visfatin and retinol-binding protein 4 (RBP4), have been suggested to play a role in insulin resistance and diabetes. This study sought to determine whether plasma concentrations of visfatin and RBP4 are altered in PCOS by comparing a total of 27 lean, norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 40 publications
5
41
0
Order By: Relevance
“…Yildiz et al (2010) showed similar RBP4 serum levels in lean Asian PCOS and weight-matched controls. Conversely, Yildizhan et al (2011) reported significantly higher RBP4 and homeostatic model assessment (HOMA) index in obese PCOS women as compared with nonobese PCOS and control groups.…”
Section: Visfatinmentioning
confidence: 58%
See 1 more Smart Citation
“…Yildiz et al (2010) showed similar RBP4 serum levels in lean Asian PCOS and weight-matched controls. Conversely, Yildizhan et al (2011) reported significantly higher RBP4 and homeostatic model assessment (HOMA) index in obese PCOS women as compared with nonobese PCOS and control groups.…”
Section: Visfatinmentioning
confidence: 58%
“…Studies have shown higher visfatin levels in PCOS women as compared with controls of similar BMI and age (Plati et al 2010, Yildiz et al 2010, Cekmez et al 2011. In those studies, PCOS patients were more insulin resistant than control women, leading to the suggestion that visfatin could be a specific marker of insulin sensitivity, possibly contributing to the pathogenesis of PCOS (Plati et al 2010, Yildiz et al 2010, Cekmez et al 2011). In contrast, recent studies do not confirm the association of visfatin with PCOS.…”
Section: Visfatinmentioning
confidence: 99%
“…Pre vi o usly, Yıl dız et al 29 showed that the le vels of RBP4 in le an, nor mal glu co se-to lerant wo men with PCOS we re not dif fe rent than the con trol gro up and RBP4 le vels we re not cor rela ted with the cli ni cal, hor mo nal or bi oc he mi cal va ri ab les. They ha ve sug ges ted that the conf lic ting re sults ob ser ved in dif fe rent stu di es may be as so cia ted with ge og rap hi cal di ver gen ce of PCOS pa tients or com mer ci al im mu no as say va ri a ti ons.…”
Section: Discussionmentioning
confidence: 87%
“…They ha ve sug ges ted that the conf lic ting re sults ob ser ved in dif fe rent stu di es may be as so cia ted with ge og rap hi cal di ver gen ce of PCOS pa tients or com mer ci al im mu no as say va ri a ti ons. 29 Re ti nol is es sen ti al for fe ma le rep ro duc ti on, and re ti no ids ha ve be en sug ges ted to play a ro le in ova ri an ste ro i do ge ne sis, oocy te ma tu ra ti on, and for ma ti on of the cor pus lu te um. The enz ymes respon sib le for re ti nol me ta bo lism are pre sent in theca cells and may be al te red in PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…In a study involving 50 women with PCOS and 28 control women, the result showed indistinguishable levels of RBP4 between the two groups [8]. In a subsequent study on 27 lean women with PCOS and 19 age-and body mass index-matched controls, RBP4 levels were also shown to be similar between the two groups [9]. RBP4 therefore appears to show similar levels between PCOS cases and control women [2].…”
Section: Description Of the Studiesmentioning
confidence: 91%